Inhibition Activity of Compounds and Bacteriophages against Flavobacterium psychrophilum Biofilms In Vitro. Issue 3 (19th June 2019) - Papadopoulou, Anna; Dalsgaard, Inger; Wiklund, Tom
Abstract: Flavobacterium psychrophilum produces biofilms under laboratory conditions, and it has been inconclusively suggested that F. psychrophilum biofilms can be a potential reservoir for transmission of the pathogen to a fish population under fish farming conditions. Therefore, there is a need for anti‐biofilm compounds. The main aim of this study was to determine the anti‐biofilm properties of certain compounds and bacteriophages on F. psychrophilum biofilms under static conditions using a standard 96‐well microtiter plate biofilm assay in vitro. Eight compounds (A‐type proanthocyanidins, D‐leucine, EDTA, emodin, fucoidan, L‐alliin, parthenolide, and 2‐aminoimidazole) at three sub‐minimum inhibitory concentrations (sub‐MICs), four bacteriophages (Fpv‐3, Fpv‐9, Fpv‐10, and Fpv‐21), and a phage combination (Fpv‐9 + Fpv‐10) were tested for inhibition of biofilm formation and reduction of the biomass of mature biofilms formed by two smooth isolates (P7‐9/10 and P1‐10B/10) and two rough isolates (P7‐9/2R/10 and P1‐10B/2R/10) of F. psychrophilum . The crystal violet staining method was used to stain the biofilms. Most of the compounds at sub‐MICs inhibited the biofilm formation of mainly smooth isolates, attaining up to 80% inhibition. Additionally, the same reduction trend was also observed for 2‐aminoimidazole, emodin, parthenolide, and D‐leucine on the biomass of mature biofilms in a concentration‐dependent manner. The anti‐biofilm properties of the compounds are believed to lie in their ability to disturb the cellular interactions during biofilm formation and probably to cause cell dispersal in already formed biofilms. Lytic bacteriophages efficiently inhibited biofilm formation of F. psychrophilum, while they partially reduced the biomass of mature biofilms. However, the phage combination (Fpv‐9 + Fpv‐10) showed a successful reduction in the biomass of F. psychrophilum mature biofilms. We conclude that inhibiting compounds together with bacteriophages may supplement the use of disinfectants against bacterial biofilms (e.g., F. psychrophilum biofilms), leading to a reduced occurrence of bacterial coldwater disease outbreaks at fish farms.